Guidelines for interactive digital storytelling presentations of cultural heritage - Rizvic, Selma; Djapo, Nermin; Alispahic, Fatmir; Hadzihalilovic, Bojan; Fejzic-Cengic, Fahira; Imamovic, Ahmed; Okanovic, Vensada (My University, 2017)
Interactive digital storytelling becomes a form of information presentation in many fields. Its application spans from media industry through digital cultural heritage, serious games, information visualization to contemporary theater and visual arts. In order to develop a new digital storytelling methodology hyper-storytelling, we engaged a team of multidisciplinary experts from computer science, visual arts, literature, film directing, psychology, communicology and human computer interaction. In this paper we present the first findings of this team in form of guidelines for interactive digital storytelling presentations of cultural heritage.